Identification the players' opinions on technical and tactical training of a handball goalkeeper - Andrei, I.; Leuciuc, F. L. (The annals of the "Stefan Cel mare" University, 2019)
The purpose of this paper is to identify the opinions of the goalkeepers regarding the specific training, an aspect that will complete the necessary information for the elaboration and experimentation of new means to increasing their sports performance. We started from the hypothesis that the argued opinions of some goalkeeper players will guide us in the elaboration of the technical and tactical training program. The study was based on the survey method. The questionnaire was applied to a number of 29 players, specialized in the position of goalkeeper. The subjects are players of the senior teams in Romania. The results showed that the technical and tactical training requires special attention in the training of the goalkeepers because its level conditions the superior results of the team in any competition